If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2) + -3y = -9 Multiply 2 * 2 4 + -3y = -9 Solving 4 + -3y = -9 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -3y = -9 + -4 Combine like terms: 4 + -4 = 0 0 + -3y = -9 + -4 -3y = -9 + -4 Combine like terms: -9 + -4 = -13 -3y = -13 Divide each side by '-3'. y = 4.333333333 Simplifying y = 4.333333333
| -50+x=-10 | | 40x-6=9 | | -4(x+3)=x+8 | | 6x(4x-1)=0 | | 5x-10x=x-12 | | 172-6x=6x+16 | | -(-2x)=(-88) | | 2(x+4)=5x-1 | | 6p+12=4p | | -4x+12=x+17 | | 12-9x=52-16x | | 3x-7=-4x | | 3x-7=-1 | | -x-6=-2 | | (x^2-9)(x+4)=0 | | 18+x=-2 | | X^4+6x=0 | | 5x-7=103 | | (x^2-2)(x^2+3)=0 | | 170-5x=6x+5 | | 5x+1=3x+13 | | -4x^2-4x+3=0 | | 6p+3=3p+12 | | q=4.5-0.5 | | P^2-6p+8= | | 5x-2=x-14 | | 58-5=8+19 | | 2(x-12)=3(x-8) | | -9x^2=100 | | 6x^2+486=0 | | 15+3x=-3 | | y+2=5y+18 |